The Social Technology Network: Analysis of the Articulation in Light of the Social Management Concept - Lemos, Marco Aurélio Cirilo; Guillaumon, Siegrid (Organizações & Sociedade, 2019)
The so-called Social Technology Network was a network articulation that gathered more than 900 organizations (as NGO´s, Associations, and Cooperatives) that proposed to organize, articulate and integrate themselves with the purpose of promoting sustainable development through the diffusion and scale reapplication of social technologies. In light of the Social Management theoretical approach, the objective of this study was to analyze this complex articulation that lasted from 2005 to 2011. A historical survey was carried out and the analytical categories of territoriality and interorganization were adopted to understand the articulation. This exploratory, descriptive, qualitative-interpretative study mobilizes different data collection techniques and primary and secondary sources. As a result, we identified that more than R 430 million were invested in projects for the reapplication of 19 social technologies and R 8 million were invested in diffusing the theme and social technologies in general. In the process of interorganization, we verified the consolidation of two instances: the first one is the Coordinating Committee as a deliberative body, and the second one, the National Forums as a propositional channel for another 900 institutions. In spite of the enormous plurality, we concluded that the Social Technology Network was a movement that worked essentially according to the strategic objectives of the supporting institutions that were part of the coordinating committee. Regarding the process of valorization of territorial aspects, despite defining macro-regional areas of action, it was not possible to verify that it acted effectively in a context of local valorization and development.